Analysis of Biophilic Architecture Concepts Application in the Kebun Pak Budi Edu-tourism Building - Musthafa, Rahmat Nur (Department of Architecture Universitas Muhammadiyah Jakarta, 2024)
Modern urban development focuses on urban areas, but the principles of urban development should be implemented in urban development, ensuring that new urban objects can be developed. These principles include economic growth, environmental conditions, community support, and technology implementation. Urban areas based on education should be developed in urban areas, such as Purwosari, to provide a unique atmosphere. However, the concept of biofilic, based on space and facilities, is also important. The